Unbelievable : a pretty little liars novel - Shepard, Sara, 1977- (New York : HarperTeen, 2008)
Four girls living in a wealthy suburb discover the identity of a stalker who has been sending them shocking text messages, and uncover the mystery of who killed their childhood friend.
Keywords: Friendship -- Juvenile fiction; Secrecy -- Juvenile fiction; Conduct of life -- Juvenile fiction; High schools -- Juvenile fiction; Mystery fiction